The barriers to whole-grain consumption among Iranian students - Mohammad Ariya; Zahra Esmaeilinezhad; Mohammad Mehdi Naghizadeh; Mohammad Mehdi Dindarloo; Farzaneh Karimi; Fatemeh Kaveh; Sahar Marzban; Kimia Hormozi; Reza Barati-Boldaji (Scientific Reports, 2022)
Abstract Studies show that regularly consuming whole grains reduce the risk of obesity and a wide range of chronic diseases. Despite this, studies reveal that students are consuming fewer whole grains. In the present study, we aimed to investigate the barriers to the consumption of whole grains among Iranian students. This cross-sectional study examined students at Fasa, Iran in 2020–2021. The online questionnaires were completed by students after receiving informed consent. Statistical analysis was performed using SPSS 26 and Chi-square, t-test, and logistic regression (P > 0.05). The current study involved 1890 students (1287 (68.1%) girls and 603 (31.9%) boys). Despite the preference for white flour bread among 53.8% of all students, 77.4% ate other whole-grain products, and 75.2% consumed all products at least once a week. Additionally, barriers such as access issues (70.5%), family supply issues (91.8%), lack appeal (72.8%), non-consumption by classmates (96.2%), and high prices in recent years (43.9%) were identified as obstacles to whole grain consumption. Furthermore, white bread eating students had significantly lower appetite levels and tended to eat fast food more often than those who ate whole grains (P < 0.05). We found that slightly more than half of the participants preferred to eat bread prepared with refined flour. Several other factors, including lack of access, lack of attractiveness, product price, parents not purchasing whole-grain products, students not paying attention to nutrition labels, peers’ effect, and eating with friends instead of family, also contribute to students avoiding whole-grain products.